The complete obsolete guide to generative AI - Clinton, David (Manning Publications, 2024)
AI technology moves so fast that this book is probably already out of date! But don't worry-The Complete Obsolete Guide to Generative AI is still an essential read for anyone who wants to make generative AI into a tool rather than a toy. It shows you how to get the best out of AI no matter what changes come in the future. You'll be able to use common automation and scripting tools to take AI to a new level, and access raw (and powerful) GPT models via API.
Online resource; title from title details screen (O'Reilly, viewed October 1, 2024)
Keywords: ChatGPT; Artificial intelligence; Natural language generation (Computer science); Neural networks (Computer science); Intelligence artificielle; Génération automatique de texte; Réseaux neuronaux (Informatique); artificial intelligence; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet